The “Big” Consequences of IFRS: How and When Does the Adoption of IFRS Benefit Global Accounting Firms? - Wieczynska, Maria (The Accounting Review, 2016)
ABSTRACT I investigate how the adoption of International Financial Reporting Standards (IFRS) affects audit markets. Specifically, I examine the effect of IFRS adoption on the likelihood and direction of auditor switching in a sample of firms from five European Union countries: the United Kingdom, Germany, Spain, Italy, and Poland during the period from 1998 through 2010. I hypothesize that IFRS adoption creates an expert advantage for global audit firms (i.e., Big 4 audit firms, Grant Thornton, and BDO) during a regime shift in reporting standards. I find that clients are more likely to switch from small to global audit firms in the year of IFRS adoption. I also hypothesize that the strength of a country's regulatory regime affects the likelihood of auditor replacement around IFRS adoption. I find that firms listed in countries with high-quality regulation and enforcement are significantly more likely to switch from small to global audit firms in the year of IFRS adoption (with the odds of the switch almost doubled when compared to non-adoption years). In weaker regulatory regimes, IFRS adoption is not associated with an increase in auditor switching. Additional tests provide evidence that global audit firms' advantage stems from their perceived IFRS expertise. Finally, the results confirm that not only Big 4, but also Grant Thornton and BDO, benefit from IFRS adoption.